The man without a shadow - Oates, Joyce Carol 1938- (Ecco, an imprint of HarperCollins Publishers, 2016)
In 1965, neuroscientist Margot Sharpe meets Elihu Hoopes: the "man without a shadow," who will be known, in time, as the most-studied and most famous amnesiac in history. A vicious infection has clouded anything beyond the last seventy seconds just beyond the fog of memory. Over the course of thirty years, the two embark on mirrored journeys of self-discovery: Margot, enthralled by her charming, mysterious, and deeply lonely patient, as well as her officious supervisor, attempts to unlock Eli's shuttered memories of a childhood trauma without losing her own sense of self in the process. Made vivid by Oates' usual eye for detail, and searing insight into the human psyche, The Man Without a Shadow is eerie, ambitious, and structurally complex, unique among her novels for its intimate portrayal of a forbidden relationship that can never be publicly revealed